Silk Fibroin as a Novel Alcohol-Resistant Excipient for Sustained-Release Tablet Formulation - Kozak, Jan; Rabiskova, Miloslava; Lamprecht, Alf (AAPS PharmSciTech, 2019)
Concomitant intake of alcoholic beverages with sustained-release oral formulations may potentially lead to dose dumping. Alcohol-resistance testing is currently a requirement for the manufacturers by regulatory authorities. Silk fibroin produced by silkworm Bombyx mori is suggested in this work as a potential alternative to a narrow spectrum of alcohol-resistant excipients. Oxycodone HCl, tramadol HCl, and flurbiprofen were selected as model drugs and formulated with regenerated silk fibroin either in the form of an amorphous solid dispersion or as a physical mixture and compressed into tablets. Preliminary compactability and tampering-resistance studies were performed. The ethanol-resistance was tested in media containing 5%, 10%, 20%, or 40% (v/v) ethanol concentration. Drug release profiles were compared using f2 similarity factor. Good mechanical tampering-resistance (tensile strength of 14.6 MPa at 400 MPa compression pressure) was obtained for tablets compressed from physical mixture. Tablets compressed from amorphous solid dispersion had lower tensile strength (2.2 MPa) but showed chemical tampering-resistance to extraction by pure ethanol (7.1% of oxycodone HCl after 24 h). Drug release is controlled predominantly by swelling and diffusion. With an increasing ethanol concentration in release medium, the tablets swelled less, resulting in a slower release. This trend was similar for all tested drugs and for both physical states formulations. No dose dumping occurred in the presence of ethanol; therefore, silk fibroin could be considered as an alternative alcohol-resistant excipient for sustained release application.
Keywords: léky s prodlouženým účinkem; fibroiny; pomocné látky; silk fibroin; Fibroins; opioids; sustained-release; tablety; Excipients; ethanol-resistant; Delayed-Action Preparations; Tablets; alcohol-induced dose dumping